Inquiry Learning Model to Improve Student's Critical Thinking in the Themes Learning Technology Development in Class III SD IT Bina Insan Batang kuis - Mawarni, Dina; Hidayat, Hidayat (Widyagogik, 2022)
This study aims to determine the success of the application of the inquiry learning learning model in increasing students' critical thinking in thematic learning of Theme 7 Technology Development in class III SD IT Bina Insan Batang Kuis. The design of this research is the Classroom Action Research (CAR) model of Kemmis and Mc. Taggart is a collaborative research conducted in 3 cycles. The data collection instruments were in the form of tests, observations, and interviews. Data analysis techniques in this study using qualitative and quantitative data. Based on the results of the study, it is known that before being given action in class, the percentage of critical thinking students is 35%, meaning that 9 out of 26 students who achieve a completeness score above the KKM 70. So the researchers took action by applying the inquiry learning model. The results of the application of the inquiry learning model run optimally as evidenced by the teacher's observations in the first cycle of 73.33 (enough), the second cycle increased by 83.33 (good) and experienced an increase in the third cycle of 93.33 (very good). The results of the first cycle of student observations from 66.66 (enough) to 87 (good) in the second cycle and obtained an increase of 90 (very good) in the third cycle. Students' critical thinking by applying the inquiry learning model to the first cycle, which obtained a completeness percentage of 53.84% (not critical), the second cycle increased to 84.61% (critical), and increased in the third cycle by 92.30% (very critical). The results of the research that researchers have done, can be seen in the acquisition of data from the cycle has increased. Thus it can be concluded that applying the inquiry learning model in thematic learning of Theme 7 Technology Development in class III SD IT Bina Insan Batang Kuis can improve students' critical thinking.  Therefore, it is suggested that teachers can apply the inquiry learning model with the aim of improving students' critical thinking.